Pengembangan Sistem E-Procurement Pada SMK Yadika Baturaja Dengan Pendekatan Extreme Programming - Nurhasan Nugroho; Riduwan Napianto; Gusri Adithama (Universitas Muhammadiyah Makassar, 2021)
At SMK Yadika Baturaja, the procurement process is still using a conventional system, this causes a complicated administrative process so that it takes a long time to procure goods. The e-Procurement system offers problem solving solutions in procurement of goods and can make it easier to connect with suppliers via the internet. To develop the e-Procurement system, the extreme programming (XP) system development method is used, which is a branch of agile development. XP is able to do software development with requirements still changing or requirements that change very quickly. From the research results show that the XP method helps in software development, this can be seen in the stages offered make it easier to determine user needs. This is confirmed by the results of the usability test showing a value of 89.25%, which indicates that the system is in a good category.Â